2010
DOI: 10.1007/s10705-010-9396-y
|View full text |Cite
|
Sign up to set email alerts
|

Using the DSSAT-CERES-Maize model to simulate crop yield and nitrogen cycling in fields under long-term continuous maize production

Abstract: Simulation models, such as the DSSAT (Decision Support System for Agrotechnology Transfer) Crop System Models are often used to characterize, develop and assess field crop production practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 57 publications
11
82
1
2
Order By: Relevance
“…Here, the RMSE was just 25-29% (n-RMSE, Table 7) of mean measured net N mineralization. There are no comparable data in the literature for net N mineralization, but n-RMSE was even two to three times larger for simulated soil mineral N in the top layer (Liu et al 2011). Here, highest deviations were observed for soil group A, the typical loess soils (Fig.…”
Section: Evaluation Via Field Mineralization Measurementsmentioning
confidence: 70%
“…Here, the RMSE was just 25-29% (n-RMSE, Table 7) of mean measured net N mineralization. There are no comparable data in the literature for net N mineralization, but n-RMSE was even two to three times larger for simulated soil mineral N in the top layer (Liu et al 2011). Here, highest deviations were observed for soil group A, the typical loess soils (Fig.…”
Section: Evaluation Via Field Mineralization Measurementsmentioning
confidence: 70%
“…According to the results of the grain yield and GPC estimations, the inverted SVCNA method estimated grain yield and GPC better than the SVLAI method (Figure 3a-d). This is because CNA is determined by actual plant N concentration and the corresponding canopy biomass of each plant organ [32,35], thus, nutrient status and plant biomass are simultaneously considered in crop growth. The joint use of LAI and CNA as state variables also obtained good estimations of grain yield and GPC, and the RMSE values between the simulated and measured grain yield and GPC were the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…The N concentration of different plant organs varies with the plant growth stage. The available N uptake from the soil depends on the soil NH4 + and NO3 − concentrations, soil water, and root growth [34,35]. The grain dry matter was derived from photosynthesis during the grain filling stage and re-translocation from the pre-stored dry matter, whereas the N accumulation of grain was derived from the direct root uptake during the grain filling stage and re-translocation from the pre-stored N uptake.…”
Section: Dssat-ceres Model Descriptionmentioning
confidence: 99%
“…Micro-fertilization APSIM [121][122][123], EPICSEAR [124], MSM [125], DSSAT [126][127][128][129][130][131] In general, the simulations of UPS for semi-arid climates are reported by only a few papers compared to the multitude of papers available on modelling/simulation. We found that 30 out of the 187 papers contained in this review specifically covered the modelling of at least one of the four selected UPS in semi-arid areas.…”
Section: Ups Models and Authors Country Cropsmentioning
confidence: 99%